2017
DOI: 10.22502/jlmc.v5i1.126
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Oral Hypoglycemic Agents and Adherence to them among Patients with Type 2 Diabetes Mellitus in Nepal

Abstract: ABSTRACT:Introduction: Oral hypoglycemic agents (OHAs) are the most common drugs used in Type 2 Diabetes Mellitus. There are various established adverse effects related to their use including hypoglycemia, weight gain, gastrointestinal disturbance, lactic acidosis, and fluid retention. However, the pattern of adverse effects related to OHAs in Nepalese patients still needs to be explored. Our study aims to determine the pattern of adverse effects resulting from the use of OHAs among Type 2 Diabetes mellitus pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Though these are very likely to improve compliance in the patient and therefore may be used once the dose adjustment in a particular patient has been achieved. Our findings correlate with the observation of previous studies where mean drugs per prescription was 2.03 17 , metformin alone was used in 49.7% 7 , combination therapy was prescribed to 60% of all prescriptions 9 and metformin was the commonly prescribed medicine and sulphonylureas were the second most commonly prescribed drug 6 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Though these are very likely to improve compliance in the patient and therefore may be used once the dose adjustment in a particular patient has been achieved. Our findings correlate with the observation of previous studies where mean drugs per prescription was 2.03 17 , metformin alone was used in 49.7% 7 , combination therapy was prescribed to 60% of all prescriptions 9 and metformin was the commonly prescribed medicine and sulphonylureas were the second most commonly prescribed drug 6 .…”
Section: Discussionsupporting
confidence: 91%
“…Evaluation of ADRs is important for the assessment of risk factors to ensure maximum benefits of drug therapy, compliance and also confirms the rational usage of drugs. Our results for ADRs were quite satisfactory and encouraging as several other studies conducted on ADDs reported ADRs about 40%, 18,19 and nearly 30% 7 and thus combination therapy was used in these study to prevent adverse reaction such as lactic acidosis caused due to metformin 20 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, persistent hyperglycaemia damages blood vessels, nerves, kidneys, eyes, among other organs and machinery of the body, resulting in devastating sequelae [48]. The currently available anti-diabetic therapies, including insulin and synthetic oral hypoglycaemic drugs such as biguanides, sulfonylureas, and glinides [12], are inaccessible, unaffordable, palliative, and cause serious side effects [48,[50][51][52]. Consequently, the search for potent, curative, safer, accessible, and affordable alternative antidiabetics is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…There are various established adverse effects related to the use of OHA (oral hypoglycemic agents) including hypoglycemia, weight gain, gastrointestinal disturbance, lactic acidosis, and fluid retention. 2 Adverse drug reactions may reduce the patient compliance (poor patient adherence towards the therapy). From a clinical/economic viewpoint, patient's poor-adherence towards OHA is associated with reduced treatment benefits and significant financial burden, Also it can cause prolonged uncontrolled diabetes with microvascular and macrovascular complications.…”
Section: Introductionmentioning
confidence: 99%